2010 IEEE International Symposium on Modeling, Analysis and Simulation of Computer and Telecommunication Systems 2010
DOI: 10.1109/mascots.2010.30
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Framework for the Analysis of the TLB Behavior in Virtualized Environments

Abstract: Due to the rising importance of virtualization, extensive efforts have gone into determining and improving the performance of workloads on virtualized platforms. This has resulted in a series of modifications to the leading architecture used in virtualized systems (x86) by adding hardware support for virtualization, the latest of which is the addition of tags and tag comparators to the x86 TLB. In this context, it is necessary to have a thorough understanding of the TLB behavior of virtualized workloads and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…It shows more than 10 times execution time without a sidecore. This is due to frequent domain switches and contention of shared resources like caches and TLBs [8], [16], [18].…”
Section: A I/o Virtualizationmentioning
confidence: 99%
See 3 more Smart Citations
“…It shows more than 10 times execution time without a sidecore. This is due to frequent domain switches and contention of shared resources like caches and TLBs [8], [16], [18].…”
Section: A I/o Virtualizationmentioning
confidence: 99%
“…If the size of a second level cache can be reduced, transistors, die area and energy would be saved. However, previous study suggested that a large cache (4 MB) is a desired feature for VM I/O processing [16]. This is because their study simulated a virtualized system that did not have a dedicated core for VM I/O tasks.…”
Section: B Cache Organization A) First Level Cachementioning
confidence: 99%
See 2 more Smart Citations
“…And the TLB entries would be swap out regularly. However, according to the locality principle [8,9], the TLB entries may be accessed again after being swapped out [10]. Thus, it is essential to store the TLB entries which are swapped out.…”
Section: B Tlb Emulationmentioning
confidence: 99%